Crystal engineering to control the magnetic interaction between weak ferromagnetic single-chain magnets assembled in a 3D framework. Issue 56 (22nd June 2016) - Su, Lei; Song, Wei-Chao; Zhao, Jiong-Peng; Liu, Fu-Chen
Abstract : A synthetic strategy of control of the arrangement and the magnetism of the SCMs by assembly of the chains into a high dimensional network was illustrated in a family of a weak antiferromagnetic chain based 3D framework. Abstract : A new single-chain-magnet (SCM), [Co4 (OMe)3 (HCO2 )2 (L)3 ·DMF] n, (L = 4-(pyridin-4-yl)benzolate) (2), was constructed by changing the spacers of a weak ferromagnetic single-chain magnet [Co8 (OMe)6 (HCO2 )4 (isonic)6 ·H2 O] n (1). By contrasting the magnetism of the two complexes, it is found that the longer the linker the stronger the magnetic properties.